Recollection of Silene vagans C.B. Clarke (Caryophyllaceae) after a span of 138 years from Nagaland, India: its typification and threat assessment - Dey, Santanu; Moaakum; Barbhuiya, Hussain Ahmed; Bendangtemsu; Yimchunger, Y. Limthure; Phukan, Mayur Mausoom; Krishna, Gopal (Phytotaxa, 2024)
Silene vagans C.B. Clarke (Caryophyllaceae) has been rediscovered after a lapse of 138 years, which is closely related to Silene khasiana Rohrb., and hitherto been documented solely through its type collection. A detailed floral description of S. vagans, lectotype and epitype designations have been provided here along with its IUCN threat status.